On the meaning of surrealism to twentieth-century culture:Enlightenment antecedents and postmodern anticipations - Santos, Acácio Luiz (Revista de Letras, 2010)
This article investigates the meaning of surrealism to the culture of the twentieth century, emphasizing the Enlightenment heritage – language as metaphor, surrealism and its interests in politics and myth, and surrealism as a prepost – modernist style. Th us, it aims to contribute to the studies on surrealism, literary avant-gardes and literature and culture. Keywords: Literary avant-gardes. Surrealism. Literature and culture. History of literature.